Prehabilitation is better than cure - Gurlit, Simone; Gogol, Manfred (Current opinion in anaesthesiology, 2019)
Purpose of review With a continuously growing number of older patients undergoing major surgical procedures, reliable parameters practicable in perioperative routine revealing those patients at risk are urgently needed. Recently, the concept of ‘prehabilitation’ with its key elements exercise, nutrition and psychological stress reduction especially in frail patients is attracting increasing attention. - Recent findings Literature search revealed a huge amount of publications in particular within the last 12 months. Although a single definition of both frailty and prehabilitation is still to be made, various players in the perioperative setting obviously are becoming increasingly convinced about a possible benefit of the program - referring to different components and measures performed. Although physiologically advantages seem obvious, there is hardly any reliable data on clinical outcomes resulting from properly performed studies. This applies especially to octogenarians; thus those at risk for adverse events the concept originally addresses. - Summary Identifying high-risk patients at the earliest possible stage and increasing their physiological reserve prior to surgery is a promising approach that seems to result in remarkable improvements for older patients. However, further studies on effectiveness in a highly heterogeneous population and agreement on a common concept are mandatory before a final judgement can be given.